A sociabilidade religiosa afro-brasileira no bairro do IPSEP - Maciel, Silvania Maria (2007)
This Dissertation is a Case Study and aims at researching on Afro-Brazilian religions sociability, in IPSEP S Quarter, departing from Relations NET WORK method: introducing friends through friends. In order to build this net-work, we took, as a nucleus, African matrix Religions religions products shop, situated in St Joseph s Quarter, in Recife s Center. We were acquainted with its i.e. shop s owners and these ones introduced us to their costumers who live in abovementioned IPSEP S Quarter and these ones i.e. costumers are priest and religiosity adherents in Quarter Terreiros , so to say in Afro-Brazilian Houses or a place, a kind of temple, a shed where afro-brazilian ceremonies, rites are celebrated. Our contact with the community always occurred at festive public rites moments, since we are in front of initiatory Religions which most of the rites in are private, reserved only for the initiade religions members. The data gathering was fulfill, through a semi participating observations and questionnaires applied to the same shop costumers and literary, bibliographical research, in general. In order to deal with rapports, relations and interrelations among social actors, we used Baechler s sociability notions, Spink s social representations discoursive practices, Foucault s Dispositif, i.e. on elements, pieces ensemble that constitue a mechanism, Darcy Ribeiro s culture conception, as a kind of understanding resource regarding to sociability